Left ventricular end-diastolic pressure predicts in-hospital outcomes in Takotsubo syndrome. (14th October 2021) - Montone, R.A; Del Buono, M; Meucci, M.C; La Vecchia, G; Camilli, M; Pedicino, D; Trani, C; Sanna, T; Niccoli, G; Crea, F
Abstract: Background: Takotsubo syndrome (TTS) is an acute and reversible form of myocardial injury often preceded by an emotional or physical stressful event. Of importance, TTS may be associated to serious adverse in-hospital complications. Coronary angiography and left ventricle angiography remain a cornerstone for TTS diagnosis. However, the prognostic role of invasively assessed left ventricular end-diastolic pressure (LVEDP) at the time of cardiac catheterization has never been investigated. Purpose: We evaluated the role of invasively assessed LVEDP for predicting in-hospital complications in TTS patients compared to the most widely used echocardiographic parameters of ventricular function. Methods: We prospectively enrolled 130 patients (mean age 71.2±11.3 years, 114 [87.7%] female) with TTS. Invasive measurement of LVEDP was performed at the time of cardiac catheterization. The rate of in-hospital complications (composite of acute heart failure, cardiogenic shock, life-threatening arrhythmias and all-cause death) was examined. Results: In-hospital complications occurred in 37 (28.5%) patients. Patients who experienced in-hospital complications had a higher prevalence of neurological trigger and lower prevalence of emotional trigger, higher LVEDP and mean E/e' ratio and lower LV ejection fraction (LVEF) values compared to those who did not experience in-hospital complications. At multivariable Cox regression, higher LVEDP (hazard ratio [HR] 1.12, 95% confidence interval [CI] [1.05–1.20], p<0.001) and lower LVEF (HR 0.95, 95% CI [0.91–0.99], p=0.011) remained independently predictors of in-hospital complications, while emotional trigger was associated to a lower risk (HR 0.24, 95% CI [0.06–0.96], p=0.044). The area under the curve (AUC) for LEVDP in the prediction of in-hospital events was 0.776 (95% CI [0.69–0.86], p<0.001, with a sensitivity and specificity of 95% and 58% using a LVEDP cut-off value of 22.5 mmHg). The AUC was significantly higher for LVEDP than for E/e' ratio (p=0.045). Conclusions: LVEDP measured at the time of cardiac catheterization may help in identifying TTS patients at higher risk of cardiovascular events during the hospitalization with relevant therapeutic implications. Of note, in the prediction of in-hospital events the LEVDP performed better than non-invasive indexes commonly used for the assessment of diastolic function. Funding Acknowledgement: Type of funding sources: None.